The Role of Sharia Pawnshop in Supporting The Growth of The Halal Industry: Opportunities and Challenges - Husna, Arinal; Asytuti, Rinda; Ramadhani, Diva Nimas; Rosalita, Dwi Mukti (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
This research discusses the role of sharia pawnshops in supporting the strength of the Islamic financial ecosystem through the halal industry. The halal industry continues to develop rapidly in this era so the role of sharia pawnshop is not overlooked in its development. This research uses a qualitative research method that uses a descriptive analysis approach that uses various sources regarding the Sharia financial ecosystem, halal business, and the function of Sharia pawnshops in facilitating the Islamic financial ecosystem. This research explains that Sharia pawnshop can be a financial solution regarding limited capital and household economics. MSMEs are an indicator of contributing to GDP in countries that are experiencing difficulties with bank loans. Sharia pawnshop can provide capital loans with fairly easy conditions, one of which is the BPKB Ar-rum product. This research found that Sharia pawnshop has carried out a lot of promotion and education to increase public interest in Sharia pawnshop through offering benefits and in-depth understanding. This is proven by innovations in Sharia pawnshop products. Qardhul Hasan, ijarah, musyarakah, ba'i muqayyadah and murabahah-based financing in sharia procurement really supports the development of the halal industry.